ICT security in tax administration - Rapid7 Nexpose vulnerability analysis - Muliński, Tomasz (Studia Informatica. System and information technology, 2021)
The article focuses on the subject of IT security in tax administration. This study presents the research on the security level of endpoints, servers, printing devices, network switches and other ICT devices using the Rapid Nexpose vulnerability scanner. We discuss the specifics of security research in public administration resulting from the laws in force in these institutions.